2004
DOI: 10.1002/bsl.613
|View full text |Cite
|
Sign up to set email alerts
|

Legal issues of professional negligence in suicide cases

Abstract: Suicide is the eleventh leading cause of death, accounting for almost 30,000 deaths each year in the United States. The loss of a patient to suicide is the most feared outcome among mental health professionals, while the fear of litigation and liability after such suicide may be a close second. This article will familiarize mental health professionals with the legal issues of professional negligence in suicide cases. We begin with an introduction to malpractice liability for suicidal patients, followed by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…3,4 Studies have identified concerns in working with individuals at risk for suicide ranging from stress and coping with emergency situations, 5 being sued for malpractice, 6 having previous experience with losing a client to suicide, 5,7,8 and possessing adequate technical and personal competence 9 to manage at-risk clients. Given that suicide is an area of great concern, suicide prevention training may be an important area for enhanced knowledge and skill development among healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Studies have identified concerns in working with individuals at risk for suicide ranging from stress and coping with emergency situations, 5 being sued for malpractice, 6 having previous experience with losing a client to suicide, 5,7,8 and possessing adequate technical and personal competence 9 to manage at-risk clients. Given that suicide is an area of great concern, suicide prevention training may be an important area for enhanced knowledge and skill development among healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…31 Physicians are not expected to be infallible in predicting suicide, but to demonstrate a reasonable degree of skill, knowledge, and care that would reasonably be expected of a practitioner of the same experience. 32 Although suicide is a multifaceted, multi-causal product that cannot be predicted reliably, 19,28,33,[34][35][36][37] the law focuses on proximate cause. 38 Mental health professionals are held responsible for identifying potential risks for suicide and preventing suicide, with the rationale that failing to assess for suicidality leads to a failure to implement management plans that could have reduced the risk.…”
Section: Legal Perspectivesmentioning
confidence: 99%
“…It seems relatively straightforward that a mental health professional does have a duty to prevent the suicide of one of his/her clients. Indeed, this theory is supported by Kockelman v. Segal (1998), in which the California Court of Appeals held that psychiatrists have a duty to attempt to prevent suicide, and this duty holds even for outpatient psychiatrists (Packman, Pennuto, Bongar, & Orthwein, 2004). However, the actions required by that duty depend on the foreseeability of the suicide.…”
Section: The Role Of Impulsivity In the Foreseeability Of Suicidementioning
confidence: 99%
“…The court ruled that the psychiatrist was not responsible for this suicide because as an outpatient, the suicide victim could not be directly monitored and kept under his therapist's control. Still, there is indication that the number of lawsuits against outpatient providers is increasing (Packman, Pennuto, Bongar, & Orthwein, 2004), and some plaintiffs are successful in proving liability. In Bellah v. Greenson (1978, California Court of Appeals), an outpatient died by suicide via overdose.…”
Section: The Role Of Impulsivity In the Foreseeability Of Suicidementioning
confidence: 99%